2012
DOI: 10.1080/0092623x.2011.606877
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Desire Discrepancy as a Predictor of Sexual and Relationship Satisfaction in a College Sample of Heterosexual Romantic Relationships

Abstract: The authors examined desire discrepancy and its effect on sexual and relationship satisfaction in a sample of 133 heterosexual couples attending a midsize university. Couples were required to be in a relationship for at least 1 year (M = 4.32 years, SD = 3.13 years); 23.7% of the couples were cohabitating. Hierarchical multiple regression results indicated that higher desire discrepancy scores significantly predicted women's (but not men's) lower sexual satisfaction after controlling for relationship satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 40 publications
4
54
1
1
Order By: Relevance
“…Participants' satisfaction with their romantic relationship was shown to be significantly related to a higher committed relationship status, higher levels of emotional intimacy, sexual desire and sexual satisfaction and to lower levels of sexual boredom. These findings are in accordance with the body of literature on the correlates of relationship satisfaction (Byers, 2005;del Mar S anchezFuentes & Sierra, 2015;Henderson et al, 2009;Mark & Murray, 2012;Sanderson & Cantor, 2001;Willoughby et al, 2011;Yoo et al, 2013). In the context of SEM use, these findings suggest that variables, other than SEM, may be (more) important to target in research and clinical practice focusing on relationship satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants' satisfaction with their romantic relationship was shown to be significantly related to a higher committed relationship status, higher levels of emotional intimacy, sexual desire and sexual satisfaction and to lower levels of sexual boredom. These findings are in accordance with the body of literature on the correlates of relationship satisfaction (Byers, 2005;del Mar S anchezFuentes & Sierra, 2015;Henderson et al, 2009;Mark & Murray, 2012;Sanderson & Cantor, 2001;Willoughby et al, 2011;Yoo et al, 2013). In the context of SEM use, these findings suggest that variables, other than SEM, may be (more) important to target in research and clinical practice focusing on relationship satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…More generally, in research on couples' relationship satisfaction a number of moderating variables have been identified, including age (King & Scott, 2005;Umberson, Williams, Powers, Chen, & Campbell, 2005); education (Karney & Bradbury, 1995); religiosity (Goddard, Marshall, Olson, & Dennis, 2012); parenthood (Adamsons, 2013;Doss, Rhoades, Stanley, & Markman, 2009;Koepke, Hare, & Moran, 1992); relationship status, i.e. whether couples are cohabiting, married or living separately (Karney & Bradbury, 1995;Tam, Lee, Har, & Chua, 2011;Willoughby, Carroll, & Busby, 2011); relationship duration (Heiman et al, 2011;Karney & Bradbury, 1995); sexual satisfaction (Byers, 2005;del Mar S anchez-Fuentes & Sierra, 2015;Henderson, Lehavot, & Simoni, 2009); sexual boredom (Tunariu & Reavey, 2003, 2007; sexual orientation (Kurdek, 2008;Mohr & Fassinger, 2006); sexual desire (Mark & Murray, 2012); and emotional intimacy (Sanderson & Cantor, 2001;Yoo, Bartle-Haring, Day, & Gangamma, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has also demonstrated that sexual satisfaction and relationship satisfaction often influence each other bidirectionally over time (Byers, 2005;Sprecher & Cate, 2004) and are highly correlated (Mark & Murray, 2012;Montesi, Fauber, Gordon, & Heimberg, 2011). Thus, it is possible that individuals who are more satisfied with their current dating relationship (perhaps due, in part, to being more characteristically mindful in the context of their relationship) are thereby more able to experience a satisfied sexual relationship with their partner.…”
Section: Mindfulness Sexual Satisfaction and Relationship Satisfactionmentioning
confidence: 81%
“…2426 Sexually dissatisfied spouses find missed satisfaction elsewhere within their social networks that may put the entire couple at risk of HIV. Most responses to sexual concurrency have focused on campaigns to discourage couples without paying attention to the root causes.…”
Section: Discussionmentioning
confidence: 99%